Education, tooth loss, and dental visits: evidence from schooling reforms - Baumeister, Sebastian E.; Listl, Stefan; Nascimento, G.G.; Nolde, M. (Journal of dental research, 2025)
Numerous studies have shown that education correlates with tooth loss and dental services use, but whether expanding educational opportunities would reduce tooth loss and improve dental attendance remains unclear given that prior studies lacked a study design to assess causality. We leveraged a policy reform, raising the school leaving age, as an instrumental variable (IV) to estimate the effect of education on edentulism and dental visits in the United States using the repeated cross-sectional data from the Behavioral Risk Factor Surveillance System (BRFSS; N = 463,878). We additionally examined the effect of education on dental visits using longitudinal data from the Survey of Health, Aging and Retirement in Europe (SHARE; N = 69,929). Applying IV probit models, we found 1 extra year of schooling reduced edentulism likelihood by 2.9 percentage points (95% confidence interval [CI]: −0.041; −0.017) and increased dental visit likelihood by 1.2 percentage points (95% CI: 0.01; 0.024) in the United States, with similar effects on dental visits in Europe. Estimates were robust to different model specifications and plausible amounts of imperfect exogeneity. Negative control analysis supported the validity of our findings. This study provides consistent evidence that extended schooling reduces edentulism risk and increases regular dental attendance.